Association of Locus Coeruleus and Substantia Nigra Pathology With Cognitive and Motor Functions in Patients With Parkinson Disease. (7th September 2021) - Prasuhn, Jannik; Prasuhn, Michelle; Fellbrich, Anja; Strautz, Robert; Lemmer, Felicitas; Dreischmeier, Shalida; Kasten, Meike; Münte, Thomas F.; Hanssen, Henrike; Heldmann, Marcus; Brüggemann, Norbert
Abstract : Objective: To investigate the contribution of substantia nigra (SN) and locus coeruleus (LC) pathology to clinical signs and symptoms in Parkinson disease (PD) by applying neuromelanin-weighted imaging. Methods: Forty-seven patients with PD and 53 matched controls underwent motor assessment, a neuropsychological test battery, and neuromelanin-weighted MRI. Patients with PD were enrolled after fulfilling the criteria for clinically established PD as defined by the Movement Disorders Society Clinical Diagnostic Criteria. Two independent raters identified SN and LC and calculated the contrast-to-noise ratio (CNR). Results: The intrarater reliability demonstrated good reliability between raters with an intraclass correlation coefficient of 0.88 ( p < 0.001) and an interrater reliability of 0.80 ( p < 0.001). Both SN and LC CNRs were lower in patients with PD ( p ⩽ 0.001) compared to controls. The CNR of SN but not of LC was strongly correlated with disease duration ( p ⩽ 0.001). Neuromelanin pathology of the pars compacta–containing dorsolateral SN correlated with Movement Disorders Society–sponsored version of the Unified Parkinson's Disease Rating Scale I, II, and III but not cognitive function. In contrast, neuromelanin pathology of LC was associated with cognitive function in all tested domains but not with motor impairment or activities of daily living. No such associations were present in controls. Conclusions: Neuromelanin imaging of the SN and LC is well-suited to map neurodegeneration in PD. Neuromelanin pathology of the SN correlates with motor dysfunction whereas LC pathology is related to cognitive impairment. Neuromelanin-weighted imaging of the LC could thus serve as an imaging marker of executive and other cognitive dysfunction in PD. Classification of Evidence: This study provides Class I evidence that neuromelanin-weighted imaging was associated with the severity of various signs and symptoms in patients with PD.